[A new chapter in the field of memory: hippocampal neo-neurogenesis]. - Dupret, D; Abrous, D (2010)
The dogma according to which "once the development of the central nervous system ended, generation of neurons was impossible" has been challenged by the discovery that new neurons are created in specific regions of the adult mammalian brain. This discovery has been one of the most controversial of modern neuroscience. One of these regions is the dentate gyrus of the hippocampal formation, a key structure in memory. Here we will review our current knowledge on the role of adult hippocampal neurogenesis in memory and in the pathophysiology of memory. In particular we will review evidence showing that adult-born neurons are required for learning and memory and that an alteration of their production rate leads to memory impairments. We also discuss how neurogenesis is finely shaped by learning for the purpose of mnemonic information processing.